Satisfaction Level Of Lazada Online Shopping Users From A Sharia Economic Perspective In Marga Jaya Village - Subhan; Imas Putri Reuni (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2025)
This study aims to find out the factors that affect the satisfaction of lazada online shopping customers in Marga Jaya village as well as the implementation of sharia economic principles in lazada online shopping in an Islamic economic perspective. This study uses a field research description approach with a qualitative method. The results of this study found that there are 8 levels of customer satisfaction of lazada online shopping in Marga Jaya village, namely: website, security, information quality, paimed mehod, service, product quality, product variety, and delivery. Then the implementation of the sharia economic principles of online shopping used is the istisna contract‟. The conclusion of this study is that the level of customer satisfaction of Lazada online shopping in Marga Jaya village is: website, security, information quality, paimed mehod, service, product quality, product variety, and delivery, and the implementation of sharia economic principles used is the istisna contract, which is a contract of sale and purchase in the form of ordering the manufacture of certain goods with certain criteria and requirements agreed between the orderer (buyer / mustashni') and the seller (maker/shani').